Rare Report of a Familial Case of Lingual Ectopic Thyroid - Akter, Yeasmin; Chowdhury, Md Sunny Anam; Hosen, M M Arif; Hossain, Md Nazmul; Mahmud, Sujon; Zerin, Fariha; Hasan, Bahalul (Bangladesh Journal of Nuclear Medicine, 2025)
Thyroid developmental defects lead to 85% cases of congenital hypothyroidism (CH). Among those, few (about 2%) cases are familial, having dominant genetic predisposition with low penetrance. A case of ectopic positioned lingual thyroid gland are reported in a little girl and her father, where a routine and simple nuclear medicine scintigraphy of thyroid gland using 99mTc-pertechnetate played a vital role. In vitro analysis of thyroid hormones and high resolution ultrasound of neck aided the diagnosis. Screening of the family members and relatives in such cases appear to be essential. Bangladesh J. Nuclear Med. 28(1): 170-173, 2025